Response of maize seedlings to the latent zinc deficiency under different Fe/Zn rati - Bákonyi, Nóra (Acta Agraria Debreceniensis, 2011)
Zinc (Zn) deficiency is a critical nutritional problem for plants and peoples all over the world. Almost half of the world’s cereal crops are deficient in Zn, leading to poor crop yield. In this study, the effect of different Fe/Zn ratio on some physiological parameters of maize seedlings were investigated on the dry matter of shoots and roots and their ratio, SPAD index and the total length of shoots. The relative chlorophyll contents significantly decreased under increasing Fe given to the Zn deficient. The results showed that the different Fe/Zn supplies decreased the total length of shoots - ranging from 9% to 65% - by latent Zn deficiency. Corresponding to several scientific findings, it was observed that the non-optimal Fe/Zn ratio of tissues take part in the evolution of latent Zn deficiency in the case of high Fe concentration.